Faktor Faktor yang Berhubungan dengan Kejadian Perdarahan Postpartum di Rumah Sakit Bakti Timah Kota Pangkalpinang Tahun 2024 - Marleni Marleni; Megawati Megawati (Pusat riset dan Inovasi Nasional, 2024)
Maternal health remains a major global challenge, particularly in developing countries where mothers are still highly vulnerable during childbirth. Postpartum hemorrhage is one of the leading causes of maternal mortality, accounting for approximately 25% of maternal deaths worldwide, and commonly occurs within the first 24 hours after delivery. This study aims to identify factors associated with postpartum hemorrhage at Bakti Timah Pangkalpinang Hospital during 2022–2023. The research applied a case-control design using secondary data obtained from medical records. The study population consisted of 1,002 mothers who gave birth at the hospital, with a sample of 104 respondents divided into 52 case subjects (mothers who experienced postpartum hemorrhage) and 52 control subjects (mothers who did not experience postpartum hemorrhage). Data were analyzed using the Chi-square test. The results showed significant relationships between maternal age (p=0.002; OR=3.600; 95% CI: 1.548–8.371), parity (p=0.000; OR=0.194; 95% CI: 0.079–0.477), and anemia (OR=5.099; 95% CI: 1.940–13.399) with the incidence of postpartum hemorrhage. The study concludes that mothers aged under 20 years and over 35 years, multiparous mothers, and mothers with anemia have a higher risk of experiencing postpartum hemorrhage.